2017
DOI: 10.1371/journal.pntd.0006111
|View full text |Cite
|
Sign up to set email alerts
|

Anthelminthic activity of glibenclamide on secondary cystic echinococcosis in mice

Abstract: Cystic echinococcosis (CE) is a worldwide parasitic zoonosis caused by the larval stage of Echinococcus granulosus. Current chemotherapy against this disease is based on the administration of benzimidazoles (BZMs). However, BZM treatment has a low cure rate and causes several side effects. Therefore, new treatment options are needed. The antidiabetic drug glibenclamide (Glb) is a second-generation sulfonylurea receptor inhibitor that has been shown to be active against protozoan parasites. Hence, we assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…JC-1 is an ideal fluorescent probe widely used to detect ΔΨm (mitochondrial membrane potential) during early apoptosis. The relative ratio of red and green fluorescence has been used to evaluate the degree of mitochondrial depolarization and viability of protoscoleces ( 35 ). Before staining, protoscoleces in the four groups were cultured for 48 h after different treatments.…”
Section: Methodsmentioning
confidence: 99%
“…JC-1 is an ideal fluorescent probe widely used to detect ΔΨm (mitochondrial membrane potential) during early apoptosis. The relative ratio of red and green fluorescence has been used to evaluate the degree of mitochondrial depolarization and viability of protoscoleces ( 35 ). Before staining, protoscoleces in the four groups were cultured for 48 h after different treatments.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the neurotransmitter beta-aminobutyric acid (GABA) has been reported to have the potential to trigger the formation of new beta cells and maintain the population of effective beta cells. Studies have demonstrated the significance of GABA in both type 1 and type 2 diabetes, where GABA can bind and interact with γ-aminobutyric acid A (GABAA) receptors on specific ion channels, leading to effective regulation of insulin secretion [ 112 ]. Further, GABA has anti-inflammatory effects in pancreatic islets to increase beta cell survival and decrease the number of toxic white blood cells [ 113 ].…”
Section: Janus Particles As a Potential Delivery System: A Case Study...mentioning
confidence: 99%
“… 12 ( Figure 1 A). 9 They are also used widely as herbicides, 13 antihelminthics, 14 and acaricides. 15 17 Antimicrobial and fungicidal activities are also attributed to sulfonylurea compounds.…”
Section: Introductionmentioning
confidence: 99%
“…(Figure A) . They are also used widely as herbicides, antihelminthics, and acaricides. Antimicrobial and fungicidal activities are also attributed to sulfonylurea compounds . Sulfonylthioureas (STUs) are also purported to have insecticidal activities and anticonvulsant properties …”
Section: Introductionmentioning
confidence: 99%